Predicting the Probability of Divorce Based on Triangulation and Mindfulness in Married Female University Students - Amirahmadi, Tahere; Jayervand, Hamdollah; Hooman , Farzaneh; Homaei , Rezvan (Advances in Nursing & Midwifery, 2024)
Introduction: Triangulation is a destructive pattern of communication where a third party becomes involved in a conflict between two people, often leading to an alliance with one against the other. Mindfulness is a mental state achieved by focusing one's attention on the present moment without judgment. By examining the relationship between these two factors on divorce probability, this research aims to identify potential early warning signs and intervention strategies. Methods: This descriptive-correlational research investigated the relationship between divorce probability, triangulation, and mindfulness among married female university students in 2023. A convenience sample of 304 participants was selected from the entire population of married female students. The research instruments included the Divorce Probability Questionnaire, Triangulation Scale, and Five Facet Mindfulness Questionnaire. SPSS-27 software was used to analyze the data collected from this study. Data were analyzed using Pearson correlation and stepwise regression to determine the associations between these variables. Results: The findings revealed a strong positive correlation between triangulation and the probability of divorce (r = 0.41, P < 0.001). Conversely, mindfulness was negatively associated with divorce probability (r = -0.37, P < 0.001). Collectively, triangulation and mindfulness explained 45% of the variance in divorce probability among the sample of married female university students. However, triangulation was found to be a more significant predictor of divorce than mindfulness. Conclusions: These findings suggest that addressing triangulation patterns, such as involving a third party in marital conflicts, is crucial for enhancing marital satisfaction and reducing the risk of divorce. While mindfulness may offer some protective benefits, its impact on divorce probability appears to be less significant in this context. These findings emphasize the need for targeted interventions that address triangulation and promote mindfulness to support marital well-being among Iranian female university students.